Effects of Soil Moisture Regime on Tomato Yield - Burlakoti, Saroj; Khanal, Amit; Regmi, Milan; K.C., Bishwas (Nepalese Horticulture, 2024)
In agriculture, understanding the role of moisture on crop growth and yield and establishing a proper moisture regime are prime factors for production. This research was conducted in the Horticulture Farm of Lamjung Campus in June-September 2019 to evaluate the effect of four irrigation regimes (25%, 50%, 75% and 100% based on field capacity) in flowering, fruiting, and yield of tomato. Each treatment was replicated ten times, considering a Completely Randomized Design under the plastic house in the spacing of 60 cm × 75 cm fitted along with drips of holes at 30 cm for irrigation. A significant effect (p<0.05) of moisture regime was found in flower cluster per plant, flowers per cluster, fruit set percentage, fruits per cluster, fruits/plant/plot, and yield per plant. The results revealed that an increase in moisture regime positively affects the yield per plant and other flowering fruiting characteristics. The average number of fruits per cluster (5.54), total number of fruits per plant (19.6) and total fruit per plot (196) were found to be significantly higher under 100% FC. The highest yield, 426.26 g/plant, was obtained under the condition of 100% FC. Thus, for more flowers, fruiting and yield tomatoes should be grown under higher moisture conditions.